Development of paraffin and paraffin/bitumen composites with additions of B2O3 for thermal neutron shielding applications. Issue 8 (3rd August 2017) - Toyen, Donruedee; Saenboonruang, Kiadtisak
ABSTRACT: In this work, paraffin and paraffin/bitumen composites with additions of boron oxide (B2 O3 ) were prepared to evaluate the viscosity, flexural, and thermal neutron shielding properties for uses as thermal neutron shielding materials. The results showed that the addition of 3 wt% or 9 wt% bitumen to paraffin increased the overall flexural properties with the content of 9 wt% bitumen having the highest values. The improvement in flexural properties made the composites less brittle, stiffer, and longer-lasting. Furthermore, different contents of B2 O3 (0, 7, 14, 21, 28, and 35 wt%) were added to paraffin and paraffin/bitumen composites to investigate the effects of the B2 O3 contents. The results indicated that an increase in B2 O3 contents improved the shielding properties but slightly reduced the flexural properties. Specifically for 5-mm paraffin and 5-mm paraffin/bitumen samples with 35 wt% of B2 O3, both samples could reduce neutron flux by more than 70%. The overall results suggested that the paraffin and paraffin/bitumen composites with additions of B2 O3 showed improved properties for utilization as effective thermal neutron shielding materials.